Effect of cortisol on the condition factor inNotopterus notopterus (Pallas) duringreproductive phases - Shankar, D S; Kulkarni, R S (Indian Journal of Fisheries, 2014)
The condition of the male Notopterus notopterus was studied during four phasesof reproductive cycle in control and after cortisol hormone treatment.Â Thecondition of the fish including condition factor (K) and somatic condition factor(Ks) was determined based on weight of the body, length of the fish and gonadweight.Â The condition factors decreased during spawning and post spawning,while increased during preparatory and pre-spawning phases.Â Â The hormonecortisol level estimated by Radioimmunoassay (RIA) technique indicated thatthe hormone was high during pre-spawning and spawning phases as comparedto other phases which may be due to the hormone involvement in metabolicactivity for spermatogenesis. In 60 Âµg cortisol treated fish further reduction inthese factors was noticed indicating that there is an active involvement of thewhole body towards expenditure of energy for reproductive activity.Â Since cortisolis a metabolic hormone, its treatment may result in the extra expenditure ofenergy for progressing reproductive activity such as spermatogenesis.